Superior shoulder suspensory complex fracture dislocation case report. Issue 3 (August 2017) - Lidgett, T.; Bate, E.; Pittock, L.
Abstract: Background: Acromioclavicular joint dislocation can be more complex than it first appears. The presented case had an unusual combination of injuries to the superior shoulder suspensory complex, which yielded some interesting learning points. Case summary: The injuries were sustained after a fall from a push bike and included acromioclavicular dislocation with coracoid process, clavicle and acromion process fractures. These were identified on the initial X-ray examination, which was followed by computed tomography for surgical planning. The injuries were successfully treated by internal fixation. Conclusion: The unexpected complexity of the injuries could have led to subtle but important findings being overlooked. This case highlights the importance of a thorough search strategy, consideration of injury biomechanics and knowledge of associated injuries. Highlights: Search for associated fractures in acromioclavicular joint dislocation. Assess the clavicle, acromion process and coracoid process in particular. Do not end the shoulder X-ray examination after seeing one injury. Both axial and cranially angulated anteroposterior projections are beneficial. Acromioclavicular joint fracture dislocation treatment may require further research.